Investigation of the effects of quercetin and xenograft on the healing of bone defects: An experimental study - Durmaz, Bekir; Gunes, Nedim; Koparal, Mahmut; Gul, Mehmet; Dundar, Serkan; Bingul, Muhammet Bahattin (Elsevier B.V., 2023)
Objective: In this study, it was aimed to histologic and immunohistochemical examined that the effects of quercetin on new bone formation and bone regeneration in critical size rat tibial bone defects. Material & methods: In the study, 56 rats were divided into 4 groups with 14 rats in each group. Control (C) (n = 14): A defect was created in the corticocancellous bone in the metaphyseal part of the tibia bones of the rats and no additional procedure was applied until the end of the experimental setup. Xenograft (X) group (n = 14): Bone defects were created in the tibia bones of the rats and the defects were filled with xenograft. No additional process was applied until the end of the experimental setup. Quercetin (Q) group (n = 14): A defect was created in the tibia bones of the rats and 0.1 mg/kg quercetin was administered by oral gavage until the end of the experimental setup dailly. Quercetin and Xenograft (Q + X) group (n = 14): A defect was created in the corticocancellous bone in the metaphyseal part of the tibia bones of the rats and the defect was filled with xenograft. Until the end of the experimental setup, 0.1 mg/kg quercetin was administered by oral gavage dailly. Rats were sacrificed after 4. and 8 week and tibial bone collected for histomorphometic analysis. Results: It was observed that the parameters related to bone healing were higher in the quercetin administered groups compared to the controls (P < 0,05). Conclusion: Quercetin given by oral gavage may increase bone healing. © 2022
Keywords: Bone defect; Bone healing; Bone regeneration; New bone formation; Quercetin